Hsa_circ_0001756 drives gastric cancer glycolysis by increasing the expression and stability of PGK1 mRNA - Qian, Long; Wang, Luman; Chen, Hao; Wang, Song; Hou, Yinfen; Xu, Li; Xia, Yabin; Xu, Maoqi; Huang, Xiaoxu (Frontiers in Immunology, 2025)
IntroductionStrategies for preventing high glycolysis in tumour cells are urgently needed. CircRNAs (circRNAs) play important roles in glycolysis. However, the mechanism underlying the effects of hsa_circ_0001756 in gastric cancer (GC) remains unclear.MethodsIn this study, we detected the expression of hsa_circ_0001756 in GC tissues and cells using quantitative real-time polymerase chain reaction (qRT PCR). Construct a silencing and overexpression vector to validate the role of hsa_circ_0001756 in GC. Pulldown and RIP experiments were conducted to verify the identification of miRNA and protein binding to hsa_circ_0001756.ResultsThe expression level of hsa_circ_0001756 in GC tissues and cells is significantly upregulated. The expression level of hsa_circ_0001756 is closely related to TNM stage and tumour size in patients with GC. The proliferation and migration of hsa_circ_0001756-expressing cells in vitro were assessed by functional experiments. Hsa_circ_0001756 was found to not only promote the expression and stability of PGK1 by binding with polypyrimidine tract-binding protein 1 (PTBP1) but also promote glycolysis through the miR-185-3P/PGK1 pathway. We found that the regulatory relationships of competing endogenous RNA (ceRNA) and RNA-binding proteins (RBPs) with hsa_circ_0001756may affect glycolysis in GC.ConclusionThis study provides a theoretical basis for designing drugs that target molecules related to energy metabolism in tumours and provides a new strategy for the clinical treatment of GC.